2024
DOI: 10.1590/1519-6984.261574
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and gut microbial evaluation of Tilapia (Oreochromis niloticus) fed on different levels of Moringa oleifera

Abstract: In current study, different feeding levels of Moringa oleifera formulated diet was compared to analyze the growth performance, feed conversion ratio, feed conversion efficiency and gut microbiology of Oreochromis niloticus. The study was comprised of four treatment groups including 4%, 8% and 12% Moringa oleifera and one control group which was devoid of Moringa leaves. The experimental trial was conducted at the Zoology laboratory of Pakistan Institute of Applied and Social Sciences, (PIASS) Kasur. The physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Studies have reported that supplementation with 10% M. oleifera had no negative effect on the growth performance of Nile tilapia [27]. A study also found that 12% of M. oleifera added to Nile tilapia diets can significantly improve growth performance [28]. However, unlike in this experiment, these two experimental fish were reared in the laboratory conditions, and the total feed intake was limited.…”
Section: Discussionmentioning
confidence: 69%
“…Studies have reported that supplementation with 10% M. oleifera had no negative effect on the growth performance of Nile tilapia [27]. A study also found that 12% of M. oleifera added to Nile tilapia diets can significantly improve growth performance [28]. However, unlike in this experiment, these two experimental fish were reared in the laboratory conditions, and the total feed intake was limited.…”
Section: Discussionmentioning
confidence: 69%
“…Beluga is an extremely rare species of the sturgeon family, which is included in the Red Book of the International Union for Conservation of Nature (IUCN). The mass of the beluga can reach a value of about 1.5 tons, in connection with which the beluga is considered to be the largest freshwater fish, occupying one of the leading positions in terms of size among bone fish [1,8].…”
Section: Resultsmentioning
confidence: 99%
“…Feed costs with normalized feeding are 1.5-2.0 kg per 1 kg of fish growth. The effectiveness of feeding largely depends on the thoroughness of control over the thermal and hydrochemical regime of water, the growth of fish, their food intake, as well as on the correctness and timeliness of adjusting the rationed feeding program, taking into account changing environmental conditions [7][8][9]. The size of the pellets should correspond to the weight of the fish (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation